Democracy, Corruption and the Politics of Spirits in Contemporary Indonesia - Syukur, Yanuardi (Universitas Islam Internasional Indonesia (UIII), 2023)
Democracy, Corruption and the Politics of Spirits in Contemporary Indonesia (London and New York: Routledge, 2014) Nils Bubandt, the author of Democracy, Corruption and the Politics of Spirits in Contemporary Indonesia, discusses three important topics in this book: democracy, corruption, and the politics of spirits in contemporary Indonesian society. In exploring these three things, Bubandt discusses through the lenses of five objects: kyai, bloggers, politicians, sultans, and prophets. Bubandt also discusses the charm of democracy, the paradox of Indonesian democracy, the ‘ghosts’ of politics in democracy such as corruption, elitism, nepotism, and patrimonialism (the ‘meeting’ between the modern political system and traditional political culture rooted in past kingdoms), and secularism. Bubandt's discussion of these interesting themes is framed within the framework of a study of the world of politics and the world of jin/unseen worlds or ‘other realms’.